PENGARUH PROMOSI, HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN PRODUK THE BODY SHOP DI MAL KOTA KASABLANKA - Darwin Raja Unggul Saragih; Ricky Talumantak; Nurul Zahra (LPPM Universitas Asa Indonesia, 2020)
This study is aimed to determine the influence of promotion, price and location on buying decision. The population in this study are the buyers of The Body Shop at Kota Kasablanka Mall. The sampling technique used is purposive due to efficiency and time limitation. The method of technique used is multiple linear regression, validity test, reliability test, classic assumption test (normality test, multicollinearity test, heteroscedasticity test, and linearity test) while the hypothesis test includes the F test, t test, partial analysis test, and the coefficient of determination (R2). The result showed that promotion, price and location on buying decisions partially and simultaneously hjave a positive effect of buying decision.